Trends in the incidence rate of genitourinary system cancers in Turkey: 2004-2015 - Yiğit, Pakize; Ataç, Ömer; Aydın, Sabahattin (AVES, 2020)
Objective: To analyze age-standardized urological cancer incidence rates in Turkey during the last twelve years based on the available published data (2004-2015).Material and methods: Cancer data were obtained from the reports of Turkish Directorate of Public Health Cancer Department for 2004-2015. A trend analysis was conducted using the joinpoint regression analysis to observe the change in the trends over time. The average annual percentage of change, annual percent change, and the corresponding 95% confidence interval were calculated.Results: Throughout the observed period, cancer incidence rates in men significantly increased by 3.04%, 4.70%, 4.03%, and 2.97% for all the genital organs, kidney, testis, and prostate, respectively. A significant increase of 3.11% and 1.91% was observed for the urinary system organs and bladder, respectively, of women during the same period.Conclusion: The increase in the incidence rate of urinary system cancers was more prominent than that of all cancers types in general. The total incidence rate of urinary system cancers (bladder and kidney) tends to increase more in women than in men. While there was no cancer with decreased incidence during the entire study period, similar decreases in some urogenital cancer types tended to occur during the second trend period.
Keywords: Genitourinary Cancer; Urogenital Neoplasms; Urologic Cancer